Aktywizacja i rozwój społeczności lokalnych i środowiskowych - Wierzbicki, Zbigniew (Wydział Prawa i Administracji UAM, 1987)
The author mentions and analyses three main elements of the process defined as the activation and development of local communities: 1. participation in common cause for the benefit of one's own community, 2. voluntary and mutual help rendered to promote higher efficiency of activity, 3. a plan of activity aimed at improving the living conditions of the community. Next, the article defines the circumstances under which a social movement for activation is to exist and function. The activation programme should take those circumstances into account. Among them the following should be mentioned in the first place: a character of macrosystem (centralized to a lesser or greater degree or decentralized), the degree of industralization and the needs of the community over a given period. An important problem is the right selection of leaders of the movement for activation. Every leader performs three roles: he is an animator, organizer and educator. An animator stimulates aspirations and needs; he stimulates the community to action. The role of an organizer consists in providing the local community with information, getting necessary means and gaining support of authorities and institutions. The educator's role does not only result from the proper fulfilment of the other two but also from the necessity of acting in the fields such as fighting social pathology, carring out education, providing care for orphans or old people, organizing sport activities, etc. According to the author, the movement for activation of local communities may be best developed in moderate macrosystems, i.e. relatively centralized or relatively decentralized, whereas the chances for its successful development decrease with growing urbanization of a local community. In big cities the said movement is unlikely to appear or in any case difficult to be realized.
The activation and development of local communities